Effect of the medium composition on the asymbiotic germination and in vitro development of the Laeliocattleya hybrid (2020)
In vitro cultivation techniques are viable alternatives for the germination and production of orchid seedlings in a short period. From another perspective, when studying the optimal germination conditions, knowing about the seeds viability is essential. Therefore, this research aimed to study the appropriate medium for germination and in vitro development of xLaeliocattleya Richard Muller. In addition, optimal preconditioning was determined to enhance the tetrazolium test. Initially, the indehiscent capsules were collected in a nursery in Bochalema-Norte de Santander. From them, seeds were obtained for the preconditioning and germination tests. One portion was subjected to different precondition treatments: distilled water, sodium hypochlorite (0.5 1.0%) and sucrose (10%). Afterwards, seeds were rinsed and exposed to different concentrations and exposure periods of tetrazolium. Regarding in vitro cultivation, the commercial medium Orchid Seed Sowing Medium, Murashige & Skoog (MS), and the MS supplemented with coconut water (MSC), pineapple juice (MSP) and gibberellic acid (MSGA3) were evaluated. The highest percentage of viability was obtained by subjecting the seeds to preconditioning with 10% sucrose and keeping them for 24 h in a 0.5% tetrazolium solution. With respect to the MS media used, those enriched with organic supplements proved to be superior to the other treatments since the highest results were achieved both in asymbiotic germination (56 § 2.8%) and in seedlings formation (25.8 § 0.8) with the MSP medium, followed by the MSC medium. In this way, a viable and low-cost alternative is offered for the commercial propagation of xLaeliocattleya Richard Muller.